Respirable dust exposure (pm2 5) and respiratory health among male quarry workers, Kelantan - Jamal, Nur Farahani Azwe (Universiti Sains Malaysia, 2016)
Exposure to workplace dust is a common problem associated with respiratory illnesses and has been an area of research interest for the last decades. A cross sectional study was carried out to determine the association of respirable dust exposure (PM25) and respiratory health among male quarry workers. This study was conducted among 50 male quarry workers and 50 male administrative workers. The investigation included spirometric testing and detailed personal interviews using structured questionnaire adopted from British Medical Research Council (BMRC) Questionnaire on respiratory symptom. Personal exposure of respirable dust was measured among the quarry workers by using TSI SidePak™ AM510. The mean personal monitoring of respirable dust among exposed group was higher at grinding bunker section (0.26±0.26 mg/m3). This result exceeding permissible exposure limits (PEL) (0.10mg/m3) 8 hours Time Weighted Average (TWA-8h) according to US Occupational Safety and Health Administrative (OSHA) and Control of Substances Hazardous to Health Regulations 2002. Respiratory symptoms reported by male quarry workers were phlegm (46.0%, n=50), dyspnea (36.0%, n=50), cough (32.0%, n=50) and chest tightness (22.0%, n=50). Age had significant relationship with the dyspnea (Adj OR: 1.564, Cl 95%: 1.049, 2.333). There was a significant different of %FEV1/FVC between quarry workers and control group. Smoking was significantly associated with FVC (b=-0.412, p<0.05) while age was significantly associated with FEV, (b=-0.026, p<0.05) and %FEV1/FVC (b—0.416, p<0.05). In conclusion, there was no association between respirable dust exposure (PM2.5) and respiratory health among the quarry workers. However, improvement on engineering control and work practices modifications should be done to reduce exposure of respirable dust to safe personal exposure.